Additive Effect of Dextrans on the Stability of Horseradish Peroxidase - Altikatoglu, Melda; Basaran, Yeliz (SPRINGER, 2011)
The influence of various concentration (10, 20, and 30% w/v) of different molar weighted dextrans as additives on the stability of HRP has been studied in aqueous medium. Native HRP preparations were formulated with different additives for storage stabilization and better performance at high temperature and pH. The results obtained show a stabilizing effect in the presence of an additive (75 kDa dextran). The enzyme with 75 kDa dextran (in concentration 10% w/v) showed the highest thermal resistance and the best performance for long-term storage at pH 5.0. In the presence of the 75 kDa dextran, the enzyme activity was increased threefold at 25 A degrees C and lost only 15% activity in 2 h at 50 A degrees C in comparison to the native enzyme which lost all its activity. In addition, dextran protected HRP against inactivation by air bubbles.
Keywords: Horseradish peroxidase; Dextran; Additive; Stability; Activity; Thermoinactivation; THERMAL INACTIVATION; BETA-GALACTOSIDASE; ENZYME STABILITY; GLUCOSE-OXIDASE; STABILIZATION; POLYOLS; THERMOSTABILITY; TEMPERATURE; INVERTASE; MECHANISM; Biochemistry & Molecular Biology